Late Onset Anaphylaxis in a Hydatid Cyst Case Presenting with Chronic Urticaria - Insu Yilmaz; Omur Aydin; Alexis Okoh; Zeynep Misirligil (Case Reports in Medicine)
Hydatid cyst is still endemic in various regions of the world. It is the most frequent cause of liver cysts worldwide. Urticaria is sometimes the first manifestation of the disease. However anaphylactic reaction and urticaria have been very rarely reported in the literature. Traditionally, surgery has been the only accepted mode of treatment; however, percutaneous treatment has recently been proposed as an alternative. Cases of anaphylaxis have been reported after percutaneous drainage of hydatid cyst. However, anaphylaxis usually develops within a few hours. Herein, we describe the case of a patient who presented with hydatid cyst causing chronic urticaria and late anaphylactic reaction following percutaneous aspiration of a liver hydatid cyst. We emphasize that physicians should be aware of hydatid cyst as a possible etiology for seemingly chronic spontaneous urticaria, especially in endemic regions. Patients should be kept under observation for at least one day due to the risk of early and late anaphylaxis after percutaneous aspiration treatment.